Preparation and photocatalytic activity characterization of activated carbon fiber–BiVO4 composites. Issue 43 (10th July 2018) - Zhang, Chencheng; Han, Pingfang; Lu, Xiaoping; Mao, Qinghui; Qu, Jiangang; Li, Ya
Abstract : Herein, we describe the hydrothermal immobilization of BiVO4 on activated carbon fibers, using Reactive Black KN-B photocatalytic performance evaluation and establishing the experimental conditions yielding maximalphotocatalytic activity. Abstract : Herein, we describe the hydrothermal immobilization of BiVO4 on activated carbon fibers (ACFs) and characterize the obtained composite by several instrumental techniques, using Reactive Black KN-B (RB5) as a model pollutant for photocatalytic performance evaluation and establishing the experimental conditions yielding maximal photocatalytic activity. The photocatalytic degradation of RB5 is well fitted by a first-order kinetic model, and the good cycling stability and durability of BiVO4 @ACFs highlight the potential applicability of the proposed composite. The enhanced photocatalytic activity of BiVO4 @ACFs compared to those of BiVO4 and ACFs individually was mechanistically rationalized, and the suggested mechanism was verified by ultraviolet-visible spectroscopy, attenuated total reflectance Fourier-transform infrared spectroscopy, and RB5 degradation experiments. Thus, this work contributes to the development of BiVO4 @ACF composites as effective photocatalysts for environmental remediation applications.